Dictionary of lexicography - Hartmann, R. R. K. (Routledge, 1998)
Dictionaries are among the most frequently consulted books, yet we know remarkably little about them. Who makes them? Where do they come from? What do they offer? How can we evaluate them?The Dictionary of Lexicography provides answers to all these questions and addresses a wide range of issues:* the traditions of dictionary-making* the different types of dictionaries and other reference works (such as thesaurus, encyclopedia, atlas and telephone directory)* the principles and concerns of lexicographers and other reference professionals* the standards of dictionary.